Analysis of Community Participation in Urban Waste Management Transformation: A Case Study of Zero Waste City Implementation in Depok City - Darmawan, Zikri Dwi; Mukhsin, Nani Nurani (Sean Institute, 2025)
The City of Depok is currently facing a serious waste management crisis, as the Cipayung Landfill has exceeded its capacity and receives approximately 1,200–1,500 tons of waste per day. In this context, community participation in waste segregation at the source plays a crucial role in reducing the pressure on landfill facilities. This study aims to examine the dynamics of community participation in waste management in Depok City and to identify the key factors that encourage and hinder such participation. Using a qualitative descriptive approach with a case study method, data were collected through field observations, in-depth interviews with waste bank managers and Black Soldier Fly (BSF) maggot processing operators, as well as an analysis of secondary data obtained from the National Waste Management Information System (SIPSN) 2024. The findings reveal that community participation in Depok is strongly driven by economic incentives, particularly through the presence of more than 400 waste banks and innovations in BSF maggot bioconversion. However, the sustainability and consistency of public participation are constrained by systemic challenges, especially the downstream waste transportation system that continues to mix segregated waste during collection and transport. Overall, the study concludes that community participation in waste management in Depok has reached a level of collective awareness, yet it requires stronger policy and logistical synchronization from the city government, particularly through the implementation of segregated waste collection schedules, to ensure long-term sustainability.